Нагласи на днешните български емигранти към родния език и родното образование - Исса, Катя (Slavica Lodziensia, 2019)
The attitudes of the numerous Bulgarian emigrants, scattered across the continents, to our language and to his use abroad are of particular importance for the Bulgarian state and language policy regarding emigration. The two questionnaires were conducted among the Bulgarian emigrant community in Sydney, Australia on one side and worldwide (where the answers came from) on the other side. In this report are commented the results of both questionnaires. Only those answers that reflect the attitudes of today’s emigrants to the use of their native Bulgarian language in daily communication and their willingness to participate in Bulgarian education abroad of their children are analyzed here. The characteristics of the attitudes of Bulgarian emigrants to their native language and Bulgarian education abroad are valuable in terms of the future work of Bulgarian linguistics and Bulgarian governmental institutions. Their main priority should be the delay of the process of forgetting the Bulgarian language from the generations.